PERAN NITRAT OKSIDA NO PADA GANGGUAN FUNGSI MOTOR DENGAN HIPERTENSI - Darwin Amir* (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION NITRIC OXIDE OR NITROGEN MONOXIDE NO IS A COLOURLESS GAS SOLUBLE IN WATER AND ORGANIC SOLVENT NO CAN DIFFUSE READILY BETWEEN AND WITHIN CELLS NO IS EXTREMELY USEFUL AS AN INTERCELLULAR SIGNALING AGENT BECAUSE IT CAN FREELY DIFFUSE BETWEEN CELLS AND SERVES TO MODULATE LOCAL CELLULAR RESPONSES MOTOR DYSFUNCTION IS A DISABILITY EXPERIENCED BY OLDER ADULTS TOGETHER WITH DISTURBANCES OF THE OTHER FUNCTIONS OF THE BODY IMPAIRED MOTOR FUNCTION IS MORE PRONOUNCED WHEN SOMEONE AT THAT PERIOD OF AGE ACCOMPANIED BY HYPERTENSION